Analisis Klausa Dalam Kalimat Majemuk Pada Novel Wedding Agreement Bab Bukan Pernikahan Impian Karya Mia Chuz : Sebuah Kajian Sintaksis - Santi Rusmayanti; Iis Ristiani (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study aims to analyze clauses in compound sentences in Mia Chuz's Wedding Agreement Novel. The research method used is qualitative descriptive research method. The descriptive method is the presentation of data based on facts as contained in the novel "Wedding Agreement" by Mia Chuz. The research technique that researchers used in this study is the analysis of clauses in compound sentences. Done by reading the novel "Wedding Agreement" by Mia Chuz. Then the novel "Wedding Agreement" by Mia Chuz was analyzed by related researchers about the clauses in compound sentences in chapter 2 of the novel. From the results of the study, there are 7 free clauses and 4 bound clauses in equivalent compound sentences. Furthermore, there are 10 free clauses and 4 bound clauses in multilevel compound sentences. So that the total number of free clauses is 17 and 8 bound clauses in compound sentences in the novel "wedding agreement" by Mia Chuz.